'Culture for Sale': The Effects of Corporate Colonization on the UK Museum Sector. Issue 3 (March 2022) - Aroles, Jeremy; Hassard, John; Hyde, Paula
For the United Kingdom, the 2008 financial crisis coupled with the subsequent economic austerity programme forced many public institutions to engage in various cost-cutting and fundraising ventures. In parallel, corporate ideologies came to dominate how academics, officials and professionals debated public activities, in turn profoundly affecting the provision of communal services. This paper explores how 'corporate colonization' ( sensu Deetz, 1992), fuelled by austerity, claims public institutions for commercial interests. Drawing on in-depth interviews with senior staff, this paper demonstrates how retrenchment of external support in the UK museum sector has been an uneven process, resulting in the manifestation of three experiential states of corporate colonization: organizational perennity, organizational perseverance and organizational precarity . We thus investigate the differential and uneven ways in which corporate colonization affects organizations pertaining to the UK cultural sector. Overall, we argue that the austerity culture in the UK affects museums in largely negative ways by forcing them to respond to the progressive need to satisfy short-term financial interests.